Mannitol Enhances the Antinociceptive Effects of Diphenhydramine as an Alternative Local Anesthetic - Jo-Young Son; Jae-Seong Lim; Jae-Hyung Park; Jae-Hyeong Park; Myeong-Shin Kim; Jung-Ho Park; Jun-suk Oh; Hyun-Wu Yoon; Jin-Sook Ju; Dong-Kuk Ahn (Pain Research and Management)
Mannitol has recently been reported to be effective in enhancing the antinociceptive efficacy of lidocaine. No single study to date, however, has compared diphenhydramine with and without mannitol for nociceptive processing as an alternative local anesthetic. In this study, we examined the antinociceptive efficacy enhancements of diphenhydramine when combined with mannitol. Male Sprague-Dawley rats weighing 230–260 g were used in a hot plate test to evaluate the antinociceptive effects of diphenhydramine. All chemicals were dissolved in isotonic normal saline and administered subcutaneously into the plantar surface of the right hind paw at 10 min before the hot plate test. A subcutaneous injection of 0.5% or 1% diphenhydramine produced significant inhibition of the withdrawal latency time compared with the vehicle treatment. Antinociceptive effects appeared 10 min after the diphenhydramine injections and persisted for over 30 min. The antinociceptive effects of 1% diphenhydramine were not statistically different from those of 1% lidocaine. Although a subcutaneous injection of a 0.5 M mannitol solution alone did not affect the withdrawal latency time, 1% diphenhydramine with 0.5 M mannitol significantly enhanced antinociception. A subcutaneous injection of 1% diphenhydramine with epinephrine (1 : 100,000) solution did not increase the antinociceptive effect of the diphenhydramine. These results suggest that diphenhydramine with mannitol can be used as an alternative local anesthetic.